The influence of remifentanil and remifentanil-plus-sevoflurane-controlled hypotension on mean arterial pressure and heart rate in children - SHirgoska, Biljana; Netkovski, Jane; Zafirova, Beti (My University, 2012)
The aim of the study is to determine the influence of remifentanil and remifentanil-plus-sevoflurane-induced anaesthesia on mean arterial pressure and heart-rate during controlled hypotension in children and to evaluate the quality of the operative field.